How Green Marketing Shapes Consumer Buying Patterns: A Systematic Review in the Philippines - Limos, Shaniah; Gonzalez, Minard Jr; Martinez, Junna (Community Development Journal, 2025)
With the growing influence of environmental crises, people have placed sustainability on top of their priorities, not just personally, but also the business sectors. Thus, Green marketing became a necessary ingredient in doing business. This systematic review consolidates existing literature on green marketing and its impact on consumer buying patterns in the Philippines. Using the PRISMA methodology, relevant studies were identified, screened, and analyzed to examine how green marketing strategies such as eco-friendly packaging, branding, promotions, and product innovations influence consumer intention and behavior. Results reveal that Filipino consumers, particularly younger generations and urban populations, increasingly show preference for sustainable products, though gaps remain due to price sensitivity, trust issues, and limited product availability. Findings provide insights for marketers and policymakers promoting sustainable consumption and aligning green marketing practices with consumer values.